The International Symposium on Islam and Democracy - Ali Bardakoglu (International Institute of Islamic Thought, 1999)
The Foundation for Research in Islamic Sciences, (known as ISAV in Turkish) has organized over tf.llrty academic, national, and intemational conferences on the issues facing the Muslim world today and has published the proceedings of these conferences. ISAV organized the last international conference in this series on November 27-29, 1998, on “Islam and Democracy.” At the outset of the symposium, Ali Ozek, the current president of ISAV, and Ali Bardakoglu, the coordinator of the symposium, made opening speeches. The representatives of some political parties and institutions made protocol speeches on behalf of their parties and institutions. Mehmet Aydm, former Dean of the School of Religion, D o h Eyiil University, Izmir, gave the first talk, titled “Religion, Politics and Democracy,” which set the tone for the conference. He dealt with three conflicting orientations on the issue. The first orientation claims that there is an intimate relationship between religion and politics; therefore, Islam requires establishment of an Islamic state. The second orientation argues that there is no relationship between digion and politics, nor should there be one. The third orientation argues that the religious may be involved in politics, that is, they may repxtsent the moral and religious values in the political arena; analogous to the Christian Democrats in some Western countries, politics should be canied on while protecting “Muslim- Democrat” identity. According to Aydm it is not appropriate to defend the first thesis because it reflects the tendency to legitimize, as the historical experience shows, an intolerant and rigid ruling system. The existence of the social demands of Islam weakens the second thesis. Likewise, the argument that Islam is incompatible with democracy because absolute rule belongs to Allah is similarly weak, it harms Islam and hinders a healthy development of democracy in Muslim societies within the framework of the rule of law because it reduced Islam to the level of secular ideologies. Similarly, it is observable that secularism has been mispemived by the two extreme ...